Real World Safety, Survival Rate, and Effectiveness of Samarium-153 (153Sm) Administration in Metastatic Castration-Resistant Prostate Cancer (mCRPC) with Bone Metastases - Chafrina, Gilberto; Pramod, Sawkar Vijay; Safriadi, Ferry; Budiawan, Hendra (Asian Pacific Journal of Cancer Care, 2025)
Background: Painful bone metastases are common in advanced prostate cancer. We report the clinical outcome after administration of Samarium-153 (153Sm), an emitter of beta-particles that concentrates in the areas of enhanced osteoblastic activity. Methods: This analysis included patients with confirmed mCRPC with bone metastases scheduled to receive 153Sm. All patients received 1 dose of 153Sm. Primary endpoints are short- and long-term safety, including incidence of bone marrow suppression. Secondary endpoints included 5 years survival rate. Results: Patients were enrolled from 2018 to 2019, and was followed up for 5 years. Out of 12 patients, 3 patients were lost to follow-up, and 9 patients were included. 9 patients (100%) had bone metastases only and received 153Sm injections. Most patients (88.9%) had high-volume osteoblastic lesions. The mean hot spot intensity decreased from 826,239.9 to 623,844.2 post-therapy (p = 0.036). Pain relief was significant, with the VAS score dropping from a median of 5 to 2 one day post-treatment (p = 0.003), and further improving to 1 thirty days later (p = 0.002). Drug-related treatment-emergent adverse events (TEAEs) occurred in 0% patients. At the 60-month follow-up, only 22.2% patients were found to be alive. The median time to death from samarium treatment end was recorded as 18 months. Conclusions: In this single-center cohort, 153Sm-EDTMP provided clinically meaningful pain palliation with acceptable safety. Survival estimates are descriptive of the underlying disease trajectory and should not be interpreted as a treatment effect given the non-comparative design and small sample. Prospective, multicenter studies using standardized pain and quality-of-life endpoints are warranted.